Rehabilitation Of Victims of Narcotics Abuse From The Perspectives of Depenalization, Decriminalization, and Human Right Protection - aritonang, jimmi marliston pandapotan; Abram Sahing; Aldhitama Ramadhan; Fredy Ied Fitriadi (International Journal of Law and Legal Ethics, 2025)
Conceptually, within the framework of depenalization, if a person who uses narcotics reports themselves to a designated Mandatory Reporting Receiving Institution (IPWL), whether at a community health center (Puskesmas) or a hospital appointed by the Ministry of Health, that person may avoid criminal prosecution.These two important principles need to be understood by all segments of society, especially those with authority and responsibility in law enforcement, namely that punishment or imprisonment is not the right solution because it only creates new problems, such as overcrowding in prisons and detention centers, along with other potential disturbances that may arise in the future.